Nursing Care of a Child with Perforated Acute Appendicitis According to the Nursing Model Based on Life Activities: A Case Report - Şan, Emine Güneş; Yıldız, Sumeyye; Öztürk, Keziban (My University, 2025)
Acute appendicitis is the most common reason for emergency abdominal surgery in children. Good outcomes are achieved in children who are diagnosed early and undergo appendec- tomy before perforation. Perforation rates are higher in children than in adults. Acute appen- dicitis, with or without perforation, is more common in children aged 1-14 years. Although common in childhood, the clinical findings of appendicitis can be atypical. For this reason, diagnosis can be difficult. The correct management of appendicitis requires a multidisciplin- ary approach. Nurses play an important role in this process, from admission to discharge. The purpose of this review is to present the nursing care of a 13-year-old pediatric patient who underwent surgery for perforated acute appendicitis, using the Life Activities-Based Nursing Model. Additionally, this case study aims to provide a nursing care plan incorporat- ing the Nursing Diagnosis Definitions and Classifications (NANDA), Nursing Interventions Classification (NIC), and Nursing Outcomes Classification (NOC). This study presents the care plan of a 13-year-old boy who underwent two operations for perforated appendicitis. The care was developed using the Roper-Logan-Tierney Life Activities-Based Nursing Model alongside NANDA, NIC, and NOC. The nursing model based on life activities helped define the scope of nursing care for the child who underwent surgery for perforated acute appen- dicitis. The level of dependency of the 13-year-old child was assessed, and activities of daily living and self-care skills were supported. By utilizing the model, the patient recognized its potential and experienced a reduction in stressors.
Keywords: Child; nursing; Appendicitis